CISSP Cert Guide, Second Edition - Abernathy, Robin M.; McMillian, Troy (Pearson IT Certification, 2016)
In this best-of-breed study guide, two leading experts help you master all the topics you need to know to succeed on your CISSP exam and advance your career in IT security. Their concise, focused approach explains every exam objective from a real-world perspective, helping you quickly identify weaknesses and retain everything you need to know. Every feature of this book supports both efficient exam preparation and long-term mastery: Opening Topics Lists identify the topics you'll need to learn in each chapter, and list (ISC)2's official exam objectives Key Topics feature figures, tables, and lists that call attention to the information that's most crucial for exam success Exam Preparation Tasks allow you to review key topics, complete memory tables, define key terms, work through scenarios, and answer review questions. All of these help you go beyond memorizing mere facts to master the concepts that are crucial to passing the exam and enhancing your career Key Terms are listed in each chapter and defined in a complete glossary, explaining all the field's essential terminology The companion website contains the powerful Pearson IT Certification Practice Test Engine, with two practice exams and access to a large library of exam-realistic questions. The compansion website also includes memory tables, lists, and other resources, all in a searchable PDF format. This study guide helps you master all the topics on the latest CISSP exam, including: Access control Telecommunications and network security Information security governance and risk management Software development security Cryptography Security architecture and design Operation security Business continuity and disaster recovery planning Legal, regulations, investigations, and compliance Physical (environmental) security.